Nummulitids, lepidocyclinids and Sr-isotope data from the Oligocene of Kutch (western India) with chronostratigraphic and paleobiogeographic evaluations. Issue 1 (1st January 2018) - Less, György; Frijia, Gianluca; Özcan, Ercan; Saraswati, Pratul K.; Parente, Mariano; Kumar, Pramod
Abstract: Due to its intermediate geographical position between the Mediterranean and W Pacific, the Oligocene shallow-marine sequence of Kutch (India) is of key importance in paleobiogeographical interpretations. Larger benthic foraminifera (LBF) are a fundamental link for the correlation between the Mediterranean shallow benthic zones (SBZ) and the W Pacific 'letter stages'. LBF were re-evaluated by morphometric studies of the internal test from five stratigraphic sections of the Maniyara Fort Formation. Based on their significant affinity to coeval fauna in the Mediterranean, they were assigned to W Tethyan SBZ zones, supported by Sr-isotope stratigraphy. In the Basal Member, traditionally considered as early Rupelian, we identified Nummulites bormidiensis, N . kecskemetii and Heterostegina assilinoides assigning it to the early Chattian SBZ 22B Zone. The Coral Limestone Member, previously considered as late Rupelian, is also assigned to this zone, for the presence of N. bormidiensis, Eulepidina formosoides - dilatata and Nephrolepidina morgani - praemarginata . Its early Chattian age (26.5–29 Ma) is further supported by Sr-isotope data. Miogypsinoides complanatus and Spiroclypeus margaritatus in the Bermoti Member (the top of the formation) document the late Chattian SBZ 23 Zone and the Sr-isotope data (22.5–24 Ma) place it close to the Oligocene–Miocene boundary.